Intercultural Postcolonial Communication in the German Translations of Selected Novels of Chinua achebe (2011)
The translation of African postcolonial literary texts into German is part of the continuing intercultural dialogue between Africa and the West. This dialogue involves the contestation of meaning and the representation of cultural identity. Previous studies on the translation of Chinua Achebe‟s works into German mainly emphasise the linguistic and cultural difficulties of textual transfer ignoring questions of asymmetry and the contestation of cultural identity in textual relations. Things Fall Apart and Arrow of God successfully recover the coherence of an African traditional culture and contest the denigration of the African in Western narratives as accultural, primitive, barbaric and even subhuman. Given also the cultural distance between the German translations and their „english‟ source texts, the study investigates how adequately the German translations convey the cultural meanings and identity markers of the source culture. The meaning theory of intercultural communication associated with I.A. Richards‟ Context Theory of Meaning, Postcolonial literary and cultural theory of Bill Ashcroft, Gareth Griffiths and Helen Tiffin and the Skopos theory of Hans Vermeer and Katharina Reiß jointly served as the theoretical framework. Richards‟s theory emphasises that meaning resides in people not in words while Ashcroft et al establish asymmetry in textual relations. Vermeer and Reiß contend that the purpose of the target text determines translation strategies. Text-based descriptive and comparative analyses of randomly selected cultural units of translation were adopted in the study.The translations of Things Fall Apart and Arrow of God are mostly inadequate to intercultural postcolonial communication. The German translations possess traces of ethnocentrism, which is compounded by the translators‟ insufficient knowledge of the source culture and faulty use of translation techniques. Errors erase identity indicators of source cultural imagery and structures of expressions, distort and misrepresent source culture beliefs and values, impose the beliefs and views of the target culture on the source culture. They further silence authorial voice, obscure or obliterate the rational capacity of the source culture, mock the source culture through incongruous substitution of words and imagery, and lost cultural knowledge and depth of cultural meaning. The translation errors appear as counter-narratives that reveal a mode of rewriting cultural identity in postcolonial literature. The claim of the source culture to a differentiated and authentic self is both considerably conceded and simultaneously subverted or minimalised in order to consolidate the impression of inferiority of the excolonised cultural identity. Intercultural Communication foregrounds cultural inequality and conflict in textual relations such that narration as dialogue emerges as a contestation of meaning and cultural identities. Implicitly, there is the need to base the translation of African literary texts from one European language to another on postcolonial and intercultural hermeneutics. This is to ensure not only the preservation of the cultural knowledge and identity carried in the African texts, but also to forestall misrepresentation and motivate a constructive, progressive dialogue of cultures which is imperative for canon formation